Developing interdisciplinary consciousness for sustainability: using playful frame reflection to challenge disciplinary bias. Issue 1 (9th December 2022) - Horn, Annemarie; van der Meij, Marjoleine G.; Willems, Willemine L.; Kupper, Frank; Zweekhorst, Marjolein B. M.
Abstract: A major challenge for interdisciplinary teamwork on complex sustainability issues is the often-conflicting disciplinary perspectives and underlying values and assumptions among collaborators. Interdisciplinary collaboration among researchers and practitioners therefore requires interdisciplinary consciousness (IC): epistemological and metaphysical understanding and appreciation of one's own and others' disciplinary views and their differences. Since it cannot be assumed that professionals have IC, there is a need for explicit training, for instance in higher education. We developed Frame Reflection Lab (FRL)—a playful intervention to stimulate the development of IC through frame reflection—and investigated its application among cross-disciplinary student teams collaborating on sustainability issues. We aimed to understand how frame reflection can contribute to enhancing IC, by analyzing the written and oral reflections of 23 Master's degree students. We found that the FRL intervention contributed to the development of IC as it sparked cognitive, affective, and critical reflection; created a safe space for reflection; helped participants to articulate values and assumptions; and balanced structure and freedom. Our findings demonstrate that to prepare sustainability professionals for interdisciplinary collaboration, deeply rooted and possibly unconscious preconceptions have to be challenged to build awareness and appreciation of disciplinary differences. This calls for explicitly facilitating affective processes, for instance using playfulness, whereas training in reflection and interdisciplinarity usually focuses on cognitive processes. These findings are promising in terms of informing and inspiring future efforts to use playful frame reflection in education, research, and practice to support interdisciplinary collaboration to address complex sustainability issues.